2007
DOI: 10.1029/2005jc003416
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic water circulation over the Mendeleev Ridge and Chukchi Borderland from thermohaline intrusions and water mass properties

Abstract: [1] Hydrographic and tracer data from 2002 illustrate Atlantic water pathways and variability in the Mendeleev Ridge and Chukchi Borderland (CBLMR) region of the Arctic Ocean. Thermohaline double diffusive intrusions (zigzags) dominate both the Fram Strait (FSBW) and Barents Sea Branch Waters (BSBW) in the region. We show that details of the zigzags' temperature-salinity structure partially describe the water masses forming the intrusions. Furthermore, as confirmed by chemical tracers, the zigzags' peaks conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
115
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(133 citation statements)
references
References 66 publications
(123 reference statements)
17
115
1
Order By: Relevance
“…This has been observed in warm regions such as the Tyrrhenian Sea in the Mediterranean [2,3] and in the western Atlantic near the Caribbean Sea [4][5][6]. Recent observations have also shown that density staircases persist over large regions of the Arctic Ocean [7][8][9][10]. It is this case that is of particular interest because the reduction in sea ice in recent years has resulted in enhanced generation of internal gravity waves (or internal waves, for short) [11,12].…”
Section: Introductionmentioning
confidence: 96%
“…This has been observed in warm regions such as the Tyrrhenian Sea in the Mediterranean [2,3] and in the western Atlantic near the Caribbean Sea [4][5][6]. Recent observations have also shown that density staircases persist over large regions of the Arctic Ocean [7][8][9][10]. It is this case that is of particular interest because the reduction in sea ice in recent years has resulted in enhanced generation of internal gravity waves (or internal waves, for short) [11,12].…”
Section: Introductionmentioning
confidence: 96%
“…These intrusions increase the TS variability and disrupt the initially smooth TS curves, which indicate interaction between ambient water masses. These features have been used to trace the origin and pathways of water masses in the Arctic Ocean (e.g., Walsh and Carmack, 2003;Rudels et al, 1994Rudels et al, , 2005Woodgate et al, 2007) and identify shelf-glacier interactions (Jenkins, 1999;Stevens et al, 2016). (iii) For the salinity range > 33.5 (> 90 m depth; low halocline; pink shaded area; Figs.…”
Section: Methods Of Ctd Clusteringmentioning
confidence: 99%
“…The presence of intrusions usually characterizes the interleaving of one water mass into another along isopycnal surfaces in frontal zones (e.g. Walsh and Carmack, 2003;Rudels et al, 2005;Woodgate et al, 2007). In the Arctic, the interleaving typically occurs along the quasi-isohaline surfaces due to the small thermal expansion coefficient of sea water at low temperatures.…”
Section: The Storm-induced Intrusions Of Cold Subglacial Watersmentioning
confidence: 99%